Case Study : Zaileha Milk Industry / Norfarhana Balqis Husin - Husin, Norfarhana Balqis (2020)
Zaileha Milk Industry is a sole proprietor which is 100% owned by Bumiputera. The company is located at Jabatan Perkhidmatan Veterinar, Jajahan Pasir Puteh, Kelantan. This company was running by Hajah Zaileha Binti Haji Musa since 1993. She started her business with her own modal, RM 30,000. The business is focused on producing milk and dadih. Zaileha’s products can be found at farmer’s market and night market sold by seller in Machang, Kota Bharu and Johor. Besides, the company also supply the milks and dadih at Petron Kota Bharu.